Fuel Cell Fed Electrical Vehicle Performance Analysis with Enriched Switched Parameter Cuk Converter - Krishnamurthy, Kumar; Devi, Vippalapalli Lakshmi (Recent Advances in Electrical & Electronic Engineering, 2024)
BackgroundThis study aims to evaluate the performance of a 1.26 kW Proton Exchange Membrane Fuel Cell (PEMFC) fed Electric Vehicle (EV) using an Enriched Switched Parameter Cuk (ESPC) converter and an Elman Back Propagation (EBP) maximum power point tracking algorithm (MPPT). The acceptance of fuel cell-fed EVs in modern society is critical to the development of a pollution-free environment. One of the significant contributors to excessive pollution is transportation on public roads using internal combustion engines powered by crude oil as their primary energy source.ObjectiveThis study identifies suitable high voltage gain DC-DC converters with minimum duty cycle operation for fuel cell-fed electric vehicle systems and develops an intelligent MPPT controller for hybrid electric vehicle applications.MethodsIn this study, MATLAB/Simulink environment is used to design a 1.26 kW PEMFC powered electric vehicle. To integrate PEMFC to BLDC motor, an Enriched Switched Parameter Cuk converter is built with a high static converter voltage gain.ResultsThe effectiveness and performance of the fuel cell-fed EV system are investigated using perturb and observe method and Elman Back Propagation MPPT approaches for various fuel cell input temperature conditions and intervals.ConclusionThis study discusses the use of low-voltage fuel cell sources with power electronic converters that are available for various high gains in the literature. The proposed ESPC is designed to reduce stress on power converter components and is intended for low-voltage FC-fed electric vehicle applications.
Keywords: Elman back propagation